THE EFFECT OF BRAND IMAGE AND BRAND EQUITY ON INTENTION TO PAY PREMIUMThere are some brands of mobile phones that command 30-40% premium in comparison to other brands for very similar configuration. There can be multiple reasons to be able to command such - Nikhil Varghese, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
There are some brands of mobile phones that command 30-40% premium in comparison to other brands for very similar configuration. There can be multiple reasons to be able to command such a premium in a market like India which has been value for money market keeping in mind socio economic indicators. This paper attempts to explore two variables out of some that may enable a firm to charge a premium namely brand image (BIM) and brand equity (BEQ). This paper also intends to explore the collective role of BIM and BEQ through conjunctive rules in relation to three combinations of primary characteristics of a phone namely camera quality and RAM, processor and design, screen size and quality of touch. Results revealed that BIM was weighted more than BEQ for camera quality than RAM . On other hand BEQ was weighted more than BIM for processor than RAM. And BEQ was weighted more than quality of touch than the screen size.